2012
DOI: 10.1007/s10853-012-6637-2
|View full text |Cite
|
Sign up to set email alerts
|

High strain rate behavior, transformation-induced plasticity and fracture toughness characterization of cast and additionally tempered Fe85Cr4Mo8V2C1 alloy manufactured using a rapid solidification technique

Abstract: This study focuses on the characterization of the microstructures of an FeCrMoVC alloy in two states (an as-cast and a heat-treated state) as well as the compressive strain rate-dependent material and fracture toughness behavior. Both microstructures consist of martensite, retained austenite and complex carbides. Tempering results in a transformation of retained austenite into martensite, the precipitation of fine alloy carbides, and diffusion processes. High yield stresses, flow and ultimate compressive stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Hongyi Zhan 116 The University of Queensland Table 3 Parameters for the modified ZA model for Ti6554 with data at 1173K included in fitting process…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hongyi Zhan 116 The University of Queensland Table 3 Parameters for the modified ZA model for Ti6554 with data at 1173K included in fitting process…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [114] and Bintu et al [115] reported that the strain hardening rate decreases at high strain rates in TWIP steels as adiabatic heating brought by high strain rate deformations will retard twinning. Russel et al [116] observed that in the Fe85Cr4Mo8V2C1 alloy higher strain rates promoted formation of martensite at the onset of deformation. Whether martensitic transformation will increase the flow stress or not depends on the hardness of martensite in relation to parent phase.…”
Section: High Strain Rate Testingmentioning
confidence: 99%
See 1 more Smart Citation